Numerical Investigations on ultimate Strength of a double hull VLCC under combined loads and initial imperfections - Lindemann, Thomas; Opeke, Bright Ebikemefa; La Ferlita, Alessandro; Mühmer, Markus; Kaeding, Patrick (Volume 2: Structures, Safety, and Reliability, 2022)
Nonlinear finite element analyses are performed to determine the ultimate strength of a double hull VLCC under pure vertical, horizontal and biaxial bending. A parametric finite element model is developed and the influence of nonlinear material behavior, mesh size and model length on the hull girder ultimate strength is demonstrated exemplarily for hogging and sagging conditions. An appropriate parameter configuration with respect to numerical efforts and accuracy is used to perform static implicit analyses for horizontal bending and biaxial load cases. Convergence is reached by using the full Newton-Raphson scheme - an incremental iterative solution approach. The results are validated against the well-established Smith method. Due to welding, initial deflections and residual stresses are produced. For the proposed finite element model initial deflections of plating and stiffeners have been considered. Furthermore, the influence of welding residual stresses on the ultimate hull girder strength is demonstrated for the different load cases. Nonlinear finite element analyses are also performed to determine the residual strength of the damaged double hull VLCC under combined loads. Different symmetric grounding damages are implemented by removing structural components of the model. Expectedly, the results show that the ultimate strength of the structure decreases as the damage extent increases.